Optimasi Konsentrasi VCO dalam Mikroemulsi O/W dengan Tiga Surfaktan sebagai Pembawa Senyawa Bioaktif - IDewaGde Mayun Permana; Lutfi Suhendra (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2015)
This research aims to get optimum VCO concentration in formula of O/W micro-emulsionby using three surfactant that will be used as bioactive delivery. Surfactant that is used is themixture Tween 80, Tween 20 and Span 80 by setting up HLB to 14. The phase of dispersionuses VCO while phase of continuous uses aquades of 80 percent. There are treated by changingthe ratio of VCO to surfactant, namely: 2.5, 5, 7.5 and 10 percent VCO. Randomized design isused in this research with treatment repeated twice. Results of the study shows that the optimumconcentration of VCO in O/W micro-emulsion with three surfactant is 7.5 percent